Effect of Fentanyl as an Adjuvant to Brachial Plexus Block for Upper Extremity Surgeries: A Systematic Review and Meta-Analysis of RCTs - Liangsong Song; Shulian Tan; Qingmin Chen; He Li (Pain Research and Management)
Objective. To assess if the addition of fentanyl to brachial plexus block has an impact on anesthetic outcomes and complication rates in patients undergoing upper extremity surgeries. Methods. We explore the PubMed, Embase, ScienceDirect, CENTRAL, and Google Scholar databases for all randomized controlled trials (RCTs) comparing adjuvant fentanyl with placebo/no drug for patients undergoing upper extremity surgery under brachial plexus block. Outcomes assessed were onset, duration of sensory and motor anesthesia, complications, and postoperative analgesia scores. Meta-analysis was conducted utilizing a random-effects model. The risk of bias was assessed using the Cochrane Collaboration’s risk of bias assessment tool 2. Certainty of evidence was assessed using GRADE. Subgroup analysis was conducted depending upon the approach of brachial plexus block and type of local anesthetic. Results. Twelve RCTs with 660 patients were included. Addition of fentanyl had no effect on onset of sensory anesthesia (11 studies; MD: 0.48; 95% CI: −1.81, 0.85; I2 = 96%; p=0.48) but significantly shortened onset of motor anesthesia (8 studies; MD: −2.36; 95% CI: −3.99, −0.74; I2 = 96%; p=0.48). Duration of sensory anesthesia (9 studies; MD: 82.81; 95% CI: 41.81, 123.81; I2 = 99%; p<0.0001) and motor anesthesia (7 studies; MD: 93.41; 95% CI: 42.35, 144.46; I2 = 99%; p=0.0003) was significantly increased with addition of fentanyl. The certainty of evidence-based on GRADE was deemed to be moderate for both onset and duration of anesthesia. The incidence of overall complications (nausea/vomiting and pruritis) was significantly higher in the fentanyl group (7 studies; OR: 2.14; 95% CI: 1.04, 4.40; I2 = 8%; p=0.04) but with low certainty of evidence. Conclusions. Adjuvant fentanyl with brachial plexus block improves the onset of motor anesthesia but not sensory anesthesia. The duration of both sensory and motor anesthesia is significantly prolonged with fentanyl by around 83–93 minutes. However, clinicians should be aware that complications such as nausea/vomiting and pruritis are increased twofold with the addition of the drug. Current evidence is limited risk of bias in the RCTs and high heterogeneity in the meta-analyses.